Cultura de tecidos e atividade antioxidante de Cyphomamdra betacea (Cav.) Sendtn - Tavares, Valquiria de Lima (My University, 2014)
Cyphomandra betacea, popularly known as "tomate árvore" or "tamarillo", is an Andean species of the Solanaceae family with high economic potential as fruit crop. The propagation of this specie is made by seeds, a system that provoke undesirable variations in fruit shape, color, plant behavior and yield, among other traits. An alternative for the production of C. betacea is in vitro propagation. In this context, the aims of the present work were to evaluate the in vitro response of different explants of C. betacea to growth regulators, as well as the determination of the antioxidant activity and phenolic content of leaves, fruits and micropropagated plants of tamarillo. The results obtained showed that micropropagation by divition of nodal segments and their culture on MS medium without growth regulators, is a feasible alternative for the production of uniform propagules from selected plants. Direct regeneration was obtained from hypocotiles segments cultivated on MS medium supplemented with 0.5 mg/L of BA, representing an alternative for C. betacea propagation. Auxins, as 2,4-D, picloram and NAA, induced callus formation from leaves and stem explants of C. betacea. However, high phenolic oxidation of both explants and calli prevented the indirect regeneration from those calli. However, indirect organogenic regeneration was obtained from stem derived calli developed in the absence of growth regulators, when transferred to MS medium with 0.5 mg/L of BA. Leaf extracts of C. betacea exhibited higher antioxidant activity than the juice obtained from mature and immature fruits. In vitro growth on BA containing media duplicated the phenolic content and the DPPH free radical scavenging prorierty, and significantly reduced the CAT-like activity.
Cyphomandra betacea, popularmente conhecida como tomate árvore ou tamarillo, é uma planta de origem andina da família Solanaceae, com alto potencial econômico como frutífera. A propagação desta espécie ocorre principalmente através de sementes, o que eleva a variabilidade genética, prejudicando a produção de mudas para cultivo em larga escala. Uma alternativa para a produção de mudas é a propagação in vitro. Neste contexto, o presente trabalho teve por objetivo avaliar o comportamento in vitro de diferentes explantes de C. betacea frente a reguladores de crescimento, assim como determinar a atividade antioxidante e conteúdo fenólico em folhas, frutos in vivo e folhas de plantas micropropagadas de tamarillo. Os resultados obtidos mostram que a micropropagação por subdivisão de segmentos nodais em meio MS sem reguladores de crescimento, é uma alternativa viável para a obtenção de plantas uniformes a partir de explantes oriundos de plantas selecionadas. Regeneração direta foi obtida através do cultivo de segmentos de hipocótilos em meio MS contendo 0,5 mg/L de BA, servindo como alternativa de propagação. Auxinas como 2,4-D, picloram e ANA induziram a formação de calos em explantes foliares e caulinares de C. betacea. Entretanto, a elevada oxidação fenólica de explantes e calos impediu a regeneração indireta de plantas a partir destes calos. Por outro lado, regeneração indireta por organogênese foi obtida de calos formados na ausência de reguladores quando transferidos para meio MS com 0,5 mg/L de BA. Extratos foliares de C. betacea apresentaram maior atividade antioxidante do que os sucos de frutos maduros e imaturos. Reguladores de crescimento influenciam a atividadade antioxidante, de folhas de plântulas in vitro. Tratamentos com BA induzem um aumento no teor de polifenóis totais e na atividade antioxidante in vitro.
Keywords: Ciências Biológicas; Biotecnologia; Tomate; Cultivo